Regulation of thylakoid protein phosphorylation at the substrate level: Reversible light-induced conformational changes expose the phosphorylation site of the light-harvesting complex II - Zer, Hagit (The National Academy of Sciences, 1999)
Light-dependent activation of thylakoid protein phosphorylation regulates the energy distribution between photosystems I and II of oxygen-evolving photosynthetic eukaryotes as well as the turnover of photosystem II proteins. So far the only known effect of light on the phosphorylation process is the redox-dependent regulation of the membrane-bound protein kinase(s) activity via plastoquinol bound to the cytochrome bf complex and the redox state of thylakoid dithiols. By using a partially purified thylakoid protein kinase and isolated native chlorophyll (chl) a/b light-harvesting complex II (LHCII), as well as recombinant LHCII, we find that illumination of the chl-protein substrate exposes the phosphorylation site to the kinase. Light does not activate the phosphorylation of the LHCII apoprotein nor the recombinant pigment-reconstituted complex lacking the N-terminal domain that contains the phosphothreonine site. The suggested light-induced conformational change exposing the N-terminal domain of LHCII to the kinase is evidenced also by an increase in its accessibility to tryptic cleavage after light exposure. Light activates preferentially the trimeric form of LHCII, and the process is paralleled by chl fluorescence quenching. Both phenomena are slowly reversible in darkness. Light-induced exposure of the LHCII N-terminal domain to the endogenous protein kinase(s) and tryptic cleavage occurs also in thylakoid membranes. These results demonstrate that light may regulate thylakoid protein phosphorylation not only via the signal transduction chain connecting redox reactions to the protein kinase activation, but also by affecting the conformation of the chl-protein substrate.